2021
DOI: 10.1101/2021.03.03.21252841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soluble angiotensin-converting enzyme 2 is transiently elevated in COVID-19 and correlates with specific inflammatory and endothelial markers

Abstract: Rationale: Angiotensin-converting enzyme 2 (ACE2) is the main entry receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but how SARS-CoV-2 interactions with ACE2 influences the renin-angiotensin system (RAS) in Coronavirus disease 2019 (COVID-19) is unknown. Objective: To measure circulating ACE2 and ACE levels in COVID-19 patients and investigate associations with risk factors, outcome and inflammatory markers. Methods and results: Soluble ACE2 (sACE2) and sACE concentrations were meas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 55 publications
2
21
1
Order By: Relevance
“…SARS-CoV-2 uses ACE2 as a functional receptor for entry into cells [ 32 ]. Circulating ACE2 is increased in patients with active COVID-19 infection compared with healthy controls [ 21 23 ]. Our analysis is the first description of circulating ACE2 in association with clinical outcomes in patients with COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 uses ACE2 as a functional receptor for entry into cells [ 32 ]. Circulating ACE2 is increased in patients with active COVID-19 infection compared with healthy controls [ 21 23 ]. Our analysis is the first description of circulating ACE2 in association with clinical outcomes in patients with COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic upregulation of IL-10 has also been shown to contribute to inflammatory diseases ( Lauw et al, 2000 ; Lu et al, 2021 ; Yaseen et al, 2020 ), thus suggesting that an initial and persistent secretion of immunosuppressive IL-10 could trigger a subsequent compensatory inflammatory response, as it may occur in the late phase of severe COVID-19. In line with this hypothesis, in COVID-19 patients, sACE (but not sACE2), which is initially lower than healthy individuals, has been shown to significantly increase with time and to display positive correlations with IL-6 and TNF-α inflammatory cytokines ( Lundström et al, 2021 ). In this regard, the so called cytokine storm is mediated by increased levels of several proinflammatory cytokines, among which TNF-α and IL-1β have been shown to induce ACE2 synthesis and/or shedding ( Clarke et al, 2014 ; Hong et al, 2009 ) that further increase sACE2 systemic release and activity, which, in this case, are independent of SARS-CoV-2 binding.…”
Section: Pathological Effects Of Ace2 Pathway Hyperactivity and Ras-mediated Positive Feed-back Loops Triggered By Sars-cov-2 Infectionmentioning
confidence: 76%
“…A confirmation that SARS-CoVs can induced an ACE2 hyperactivity comes from recent reports showing an increase of systemic ACE2 activity in COVID-19 patients and in accordance to disease severity ( Nagy et al, 2021 ; Patel et al, 2021 ; Reindl-Schwaighofer et al, 2021 ). Similarly, high circulating levels of sACE2 were significantly associated with worse or longer COVID-19 outcome in hospitalized patients ( Kragstrup et al, 2021 ; Lundström et al, 2021 ; Reindl-Schwaighofer et al, 2021 ). Notably, in healthy individuals circulating ACE2 activity is usually undetectable ( Lew et al, 2008 ), instead pre-existing high levels of circulating ACE2 protein/activity are typical of patients with comorbidities (e.g.…”
Section: Sars-cov-induced Ace2 (And Adam17) Zinc-metalloprotease Systemic Hyperactivity As a Possible Pathophysiological Origin Of Covid-mentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, it has also been observed that soluble ACE2 may contribute to COVID-19 susceptibility, although its significance remains uncertain. In this sense, subjects with obesity and patients with COVID-19 have higher serum ACE2 levels [ 56 , 57 , 58 , 59 ]. The increased soluble ACE2 levels in COVID-19 patients may result from the cellular lysis that occurs when a severe infection takes place.…”
Section: Influence Of Obesity and Ace2 In Covid-19 Beyond Ace2 Expressionmentioning
confidence: 99%